Comparative Study of Palashgudavarti and Diclofenac Sodium Suppository in the Management of Acute Fissure in Ano (Parikartika)-An Ayurvedic Management Protocol (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background - Anal Fissure is one of the major causes for pain at anal region. The two primary signs ofthis disease are pain and bleeding, and pain is often unbearable. In males anal fissure typically occursin the midline posterior- 90 %, and 10 % midline anterior. Subsequently, female fissures on the midlineanteriorly are significantly more frequent than posteriorly (60:40). In contemporary sciences Parikartikacan be correlated with Fissure in Ano. Objective- The objective of the prospective study is to find theefficacy of Palashgudavarti & Diclofenac Sodium Suppository in the management of Acute Fissure inano(Parikartika).Material & Method: The present study is designed as a Randomized single blind parallelin which 60 patients will be enrolled. Varti will be applied for local application once a day. Assessment willbe done 0th, 7th day, 14thday, and 28th day. Results: The changes are expected to be observed in subjectiveparameters such as pain bleeding per rectum with itching as well as with objective parameters such asParikartika Healing. Conclusion: The study is expecting the nonsurgical management of fissure in ano withrespect to the impact of Palashgudavarti & Diclofenac Sodium Suppository. The research is expecting to bebaseline and benchmark of the prospective studies in Acute Fissure in ano (Parikartika).